Assessment of thymidylate synthase expression in biopsy specimens and corresponding resection specimens of non-small-cell lung cancer - Herpel, Esther; Schnabel, Philipp Albert; Steins, Martin; Dienemann, Hendrik; Herth, Felix; Thomas, Michael; Schirmacher, Peter; Warth, Arne (Histopathology, 2012)
Aims: Pemetrexed (Pem) is a potent inhibitor of thymidylate synthase (TS), and has shown efficacy in the treatment of non-small-cell lung cancer (NSCLC). TS expression in NSCLC biopsy specimens may correlate with the tumour responses to TS-inhibiting agents. As TS is not homogeneously expressed, our aim was to test whether TS expression in biopsy specimens may be representative for the whole tumour and can be used for therapeutic assessment. Methods and results: We immunohistochemically analysed TS expression in biopsy and corresponding resection specimens of 100 consecutive NSCLCs. The samples were subgrouped according to TS expression levels, and the degree of agreement between the biopsy and the corresponding resection specimen was calculated. TS expression-based grouping according to one cut-off criterion (high or low expression) led to concordant results between biopsy and resection specimens. When more than one cut-off criterion was used, the results were significantly different. Conclusions: Thymidylate synthase expression levels in NSCLC biopsy specimens may correspond to TS expression of the whole tumour when robust scoring systems are applied. Further studies are needed to determine whether high or low TS expression in NSCLC biopsy specimens is of predictive value, and whether it may allow the selection of patients who will benefit from Pem treatment.